IBU, IBU dan IBU : Ekspresiku dalam Seni Grafis Teknik Cukil Karet Dan Cetak Saring - Ramdani, Yadi (2013)
Ibu adalah sebagian kecil sebutan untuk seorang wanita yang telah melahirkan kita, kata "Ibu" jika merujuk pada akar kata Arab terambil dari kata "Al umm". Secara etimologi "al umm" adalah ashl al sya'i (asal atau pangkal sesuatu). Ketika dikatakan, umm al insan maka artinya adalah asal manusia yang darinya manusia keluar. Peranan ibu terhadap anak adalah sebagai pembimbing kehidupan di dunia ini. Peranan ibu diantaranya pemberi aman dan sumber kasih sayang, mendoakan anak-anaknya,menyusui, mengasuh dan merawat. Karya seni grafis yang di buat oleh penulis menggunakan teknik grafis cukil karet dan cetak saring pada media kertas. Teknik cetak saring merupakan seni grafis yang mempunyai karakter yaitu apabila objek sudah dicetak, maka hasilnya hampir mirip dengan sketsa awal yang ada pada kertas dan dipertegas dengan outline menggunakan teknik cukil kayu.Hasil karya yang telah penulis ciptakan adalah "Ibu adalah Wanita Kepercayaan Tuhan", "Pengorbanan yang Tak Ternilai", "Perawat dan Menjaga Anak", "Dalam Sepertiga Malam", "Semangat Bekerja Keras", dan "Dia yang Tulus". Dalam karya "Ibu adalah Wanita Kepercayaan Tuhan" penulis mengangkat gambar ibu kandung sendiri dengan mengambil sudut pandang close up. Karya kedua "Pengorbanan yang Tak Ternilai" , karya ketiga "Perawat dan Menjaga Anak" dan keenam "Dia yang Tulus", penulis memvisualisasikan sosok seorang ibu yang sedang merawat anaknya. Sedangkan dalam karya keempat "Dalam Sepertiga Malam" dan karya kelima "Semangat Bekerja Keras" terlihat jelas dalam karakter seorang ibu yang tak kenal lelah untuk berjuang demi anaknya. Keenam karya tersebut memiliki tema-tema yang diusung dari peranan dan perjuangan ibu. Sebagai inspirasi dalam karya grafis serta warna pada setiap karya yang merefleksikan makna dari unsur-unsur tersebut. Sosok ibu yang digambarkan oleh penulis merupakan karya seni grafis yang memberikan kesan bebas dan spontan, serta diperkuat penggunaan teknik linocut untuk outline yang tegas memberikan fokus objek berkesan jelas. ABSTRACT Final assignment made by the author titled MOTHER, MOTHER, AND MOTHER (GRAPHIC ARTS EXPRESSION TECHNIQUES LINOCUT AND TUSCHE) which aims (1) to express the idea of the mother through the medium of printmaking techniques tusche screen printing technique and high print woodcut technique rubber (Linocut) ( 2 ) to analyze works of graphic art screen printing techniques and printing techniques tusche high rubber woodcut techniques (Linocut) in the thematic of the mother. Fraction mother is a term for a woman who has given birth to us, the word " mom " if refers to the root of the Arabic word drawn from the word " Al- umm ". Etymologically " umm al " is ashl al sya'i (origin or base of something). When it is said, umm al insan then the meaning is of human origin from which the man out. Role of mother as mentors to children is life in this world. Role of mothers giving them a safe and source of love, pray for their children, breastfeeding, parenting and caring. Graphics art work created by the author using graphical techniques and rubber woodcut print on paper media filter. Technique screen printing is a printmaking that has a character that is, if the object is already printed, then the result is almost similar to that of the initial sketch paper and accented with outline using woodcuts . The work that has been created is the author of " Mothers are Women Trust God ", " Sacrifice is Priceless ", " Nurses and Keeping Children ", " In the third Night ", " The spirit of hard work ", and "He is sincere ". In the work " My mother is the Woman Trust God " author 's mother raised the image itself by taking a close-up viewpoint. Second work " The sacrifice Priceless ", the third masterpiece " Keeping Nurses and Child " and the sixth "He is Sincere ", the authors visualize the figure of a mother who was caring for her child. While the work of four " In the third Night " and the work of the fifth " The spirit of hard work " is clearly seen in the character of a mother for her tireless fight for his son. Sixth these works have brought the themes of the role and struggle of the mother. As inspiration in the works of graphic and color of each piece that reflects the significance of these elements. Mother figure described by the author is a graphic artwork that gives the impression of free and spontaneous, and reinforced the use of techniques to outline a clear Linocut provide a clear focus memorable objects . Keywords : Graphic Arts, Tusche, Linocut, mother figure